Stainproof member, member for in vitro diagnostic device and method for manufacturing stainproof member
By using hydrolysate products of silane coupling agents or condensates of phosphoric acid derivatives in the anti-pollution film, and controlling the zeta potential and surface chemical structure of the film, the problem of insufficient durability of the anti-pollution film to alkaline cleaning liquid is solved, and the anti-pollution effect with low protein adsorption and high durability is achieved. It is suitable for in-body diagnostic equipment that is used repeatedly.
Patent Information
- Application Number
- JP2023144815
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-06
- Publication Date
- 2025-03-18
AI Technical Summary
When using anti-pollution members in the prior art, the anti-pollution film has insufficient durability to alkaline cleaning liquid, resulting in a degradation of anti-pollution performance.
A membrane structure is adopted, in which the membrane is composed of hydrolysate of silane coupling agent or agglomerate of phosphoric acid derivatives, and by controlling the zeta potential and surface chemical structure of the membrane, the membrane is ensured to durability and low protein adsorption properties in an alkaline environment.
It realizes the reuse of anti-pollution films under high accuracy, ensures low protein adsorption and durability, and is suitable for multiple use scenarios such as in vivo diagnostic equipment.
Smart Images

Figure 2025037716000037 
Figure 2025037716000038 
Figure 2025037716000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an antifouling member, a member for in-vitro diagnostic devices, and a method for producing an antifouling member. [Background technology]
[0002] Unlike single-use devices such as pacemakers, catheters, and guidewires, components that can be used multiple times, such as forceps, endoscopes, dental drills, and in-vitro diagnostic device components, are reused after appropriate cleaning and sterilization. However, to ensure safety, the cleaning load is large, and there is a demand for components that can be used multiple times and have antifouling properties to reduce the load.
[0003] Among in-vitro diagnostic devices that can be used multiple times, trace amounts of protein adhesion can cause a decrease in detection sensitivity and reproducibility in in-vitro diagnostic device components such as biochemical analyzers. Until now, the effects of protein adsorption have been reduced by washing the components with alkali between samples. However, in recent years, there has been a trend toward higher sensitivity, and there is concern that the effects of protein adhesion cannot be completely eliminated by washing the components in the past, so there is a demand for anti-fouling coatings for in-vitro diagnostic device components.
[0004] In this situation, surface treatment agents have been widely proposed that can impart hydrophilicity, biocompatibility, antithrombogenicity, and the like to surfaces by treating the surfaces of various members with polymers of betaine monomers. Patent Document 1 proposes a method for treating medical devices such as catheters and guidewires with a silane coupling agent having a vinyl group and then polymerizing a sulfobetaine monomer, in order to improve and maintain the sliding properties of the devices. Furthermore, Patent Document 2 proposes a medical material having a polymer brush formed using a carboxybetaine monomer, and a medical instrument using the medical material. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 6154370 [Patent Document 2] Patent No. 5349873 Summary of the Invention [Problem to be solved by the invention]
[0006] However, according to the investigations of the present inventors, the methods described in Patent Documents 1 and 2 have a problem in terms of durability against an alkaline cleaning solution used for cleaning antifouling members. Therefore, an object of the present invention is to provide an antifouling member that can achieve both low protein adsorption and durability. Another object of the present invention is to provide a method for producing an antifouling member that can achieve both low protein adsorption and durability. [Means for solving the problem]
[0007] The above object can be achieved by the present invention. An antifouling member having a film provided on a substrate, the film has a condensate of a hydrolyzate of a silane coupling agent or a condensate of a phosphonic acid derivative, The film does not contain halogen atoms, The zeta potential of the membrane is -10.0 mV or more and 10.0 mV or less in water at pH=7; In an X-ray photoelectron spectroscopy analysis (ESCA measurement) of the substrate, the amount of C atoms (atomic %) / the amount of atoms of element X that are most abundant on the substrate surface (atomic %) is defined as A, and in an X-ray photoelectron spectroscopy analysis (ESCA measurement) of the film on the substrate, the amount of C atoms (atomic %) / the amount of atoms of element X (atomic %) is defined as B, in which the value of B / A is 2.0 or more and 5.0 or less. Effect of the Invention
[0008] The antifouling member of the present invention is capable of achieving both low protein adsorption and durability, and therefore is capable of performing highly accurate measurements and being used repeatedly as a member for in-vitro diagnostic devices. [Brief description of the drawings]
[0009] [Figure 1] FIG. 1 is a schematic diagram showing an example of an application of the present invention. [Diagram 2] FIG. 13 is a schematic diagram showing another example of an application of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The present invention will be described in detail below with reference to preferred embodiments. [First embodiment] The first embodiment relates to an antifouling member. The antifouling member of the present invention is an antifouling member having a film provided on a substrate, the film has a condensate of a hydrolyzate of a silane coupling agent or a condensate of a phosphonic acid derivative, The film does not contain halogen atoms, The zeta potential of the membrane is -10.0 mV or more and 10.0 mV or less in water at pH=7; In an X-ray photoelectron spectroscopy analysis (ESCA measurement) of the substrate, the amount of C atoms (atomic %) / the amount of atoms of element X that is most abundant on the substrate surface (atomic %) is defined as A, and in an X-ray photoelectron spectroscopy analysis (ESCA measurement) of the film on the substrate, the amount of C atoms (atomic %) / the amount of atoms of element X (atomic %) is defined as B, where the value of B / A is 2.0 or more and 5.0 or less.
[0011] The antifouling member satisfying the above-mentioned constitution can achieve both low protein adsorption and durability. The antifouling member of the present invention is an antifouling member having a film provided on a substrate. Conventionally, antifouling members have been produced by polymerizing a betaine monomer with a silane coupling agent having a vinyl group. However, the effect was insufficient for antifouling members that require durability against alkaline cleaning solutions, such as antifouling members. As a result of intensive research, the present inventors have clarified that durability against alkaline cleaning solutions can be exhibited by controlling two parameters within the specified ranges.
[0012] In the antifouling member of the present invention, the film does not contain halogen atoms. One of the parameters indicating that the film does not contain halogen atoms is that the ion amount of halogen atoms / total ion amount is 0.02 or less in TOF-SIMS measurement of the film. In TOF-SIMS measurement, information on elements or molecular species present at a depth of several nm or less from the sample surface can be obtained with very high detection sensitivity. Therefore, in TOF-SIMS measurement of the film, information on elements or molecular species present on the outermost surface of the film can be obtained. The ion amount of halogen atoms / total ion amount of 0.02 or less indicates the state of halogen present on the outermost surface of the film, and if it is 0.02 or less, good durability can be exhibited. This ion amount of halogen atoms / total ion amount of 0.02 or less is merely a guideline, and means that halogen atoms are not clearly detected in the film in TOF-SIMS measurement, so it is sufficient if the ion amount of halogen atoms / total ion amount is at the background level (level at which halogen atoms are not detected) in TOF-SIMS measurement.
[0013] The present inventors consider the reason for this to be as follows. In the case where the film in this configuration has a halogen, the halogen is present in a state of being bonded to carbon. Here, since the main component of the alkaline cleaning solution is water, it is considered that the halogen and the carbon bonded to the halogen are polarized and are easily solvated by water. That is, it is considered that a film having a halogen on the outermost surface has a higher affinity with the alkaline cleaning solution than a film without a halogen. It is generally known that the condensation product of the hydrolyzate of the silane coupling agent or the condensation product of the phosphonic acid derivative is eluted in an alkaline solution. Therefore, it is considered that the film having a halogen will deteriorate due to the elution of the condensation product of the hydrolyzate of the silane coupling agent or the condensation product of the phosphonic acid derivative due to the high affinity with the alkaline cleaning solution, and the durability will become insufficient. Therefore, in order to exhibit sufficient durability, it is important that, for example, the ion amount of the halogen atom / total ion amount is 0.02 or less.
[0014] In the antifouling member of the present invention, when the amount of C atoms (atomic%) / the amount of atoms of element X contained most abundantly on the surface of the substrate (atomic%) is defined as A in an X-ray photoelectron spectroscopy analysis (ESCA measurement) of the substrate, and the amount of C atoms (atomic%) / the amount of atoms of element X (atomic%) is defined as B in an X-ray photoelectron spectroscopy analysis (ESCA measurement) of the film on the substrate, the value of B / A is 2.0 or more and 5.0 or less. In the ESCA measurement, photoelectrons generated from the outermost surface to a depth of about 10 nm are detected. The value of B / A provides information on the density and film thickness of the film, and if it is 2.0 or more and 5.0 or less, good low protein adhesion and durability are exhibited. If it is less than 2.0, hydrophilicity is insufficient due to insufficient film density and film thickness, and low protein adhesion is not sufficiently exhibited. On the other hand, if it exceeds 5.0, the film thickness becomes thick and hydrophilicity is sufficiently exhibited, and low protein adhesion is exhibited, but the affinity with the alkaline cleaning solution becomes too high, and film deterioration caused by the elution of the condensation product of the hydrolysis product of the silane coupling agent or the condensation product of the phosphonic acid derivative progresses, and durability becomes insufficient. Therefore, it is important that the value of B / A is 2.0 or more and 5.0 or less.
[0015] The antifouling member in the present invention is a member that can be reused after appropriate cleaning and sterilization, such as forceps, endoscopes, dental drills, and in-vitro diagnostic device members. Among such antifouling members, in-vitro diagnostic device members are preferred because they are susceptible to the adhesion of trace amounts of protein and can effectively exert the effects of the present invention.
[0016] In addition, the antifouling member of the present invention has a film that is a condensate of a hydrolyzate of a silane coupling agent or a condensate of a phosphonic acid derivative. The condensate of the hydrolyzate of the silane coupling agent or the condensate of the phosphonic acid derivative preferably forms a covalent bond with the substrate, and preferably has a vinyl group in the molecule. As long as these conditions are satisfied, there is no particular limitation, and a conventionally known silane coupling agent or phosphonic acid derivative can be used. In the antifouling member of the present invention, it is preferable from the viewpoint of durability that the silane coupling agent is at least one selected from the group consisting of 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, 3-(methacryloyloxy)propyltriethoxysilane, 3-(acryloyloxy)propyltriethoxysilane, vinyltrimethoxysilane, triethoxyvinylsilane, allyltrimethoxysilane, allyltriethoxysilane, and (triethoxysilyl)methyl methacrylate. In the antifouling member of the present invention, the phosphonic acid derivative is preferably at least one selected from the group consisting of 2-methacryloyloxyethyl acid phosphate, 2-acryloyloxyethyl acid phosphate, 2-(methacryloyloxy)ethyl phosphate, and acid phosphoxy polyethylene glycol monomethacrylate, from the viewpoint of durability. Among these, 3-(methacryloyloxy)propyltrimethoxysilane and 2-methacryloyloxyethyl acid phosphate are preferred from the viewpoint of achieving both low protein adsorption and durability.
[0017] Furthermore, the antifouling member of the present invention has a zeta potential at pH=7 of -10.0 mV or more and 10.0 mV or less. The mechanism of protein adsorption to a substrate or the like is due to two factors: electrostatic interaction and hydrophobic interaction. Therefore, in order to suppress protein adsorption due to electrostatic interaction, it is important to control the zeta potential at pH=7 within the above range. Any material may be used as long as the zeta potential can be controlled within the above range, but it is preferable to control it by one or a combination of two or more of the following three structural features:
[0018] First, as a first structural feature, the antifouling member of the present invention preferably has a monomer having a polarity opposite to that of the substrate, and a copolymer of a hydrophilic monomer and a crosslinking agent in the membrane. According to this means, the surface charge of the substrate is cancelled by the monomer having a polarity opposite to that of the substrate. In addition, crosslinking enhances the substrate shielding ability of the membrane, making it possible to make the membrane less susceptible to the effects of the charge on the substrate surface. Furthermore, by copolymerizing a hydrophilic monomer, the low protein adsorption resulting from hydrophobic interactions can also be reduced. The copolymerization ratio of the monomer having a polarity opposite to that of the substrate and the copolymer of a hydrophilic monomer and a crosslinking agent is preferably adjusted so that the zeta potential at pH=7 is -10.0 mV or more and 10.0 mV or less.
[0019] Here, the antifouling member of the present invention may use any monomer having a polarity opposite to that of the substrate, but an amine monomer is preferred. In the antifouling member of the present invention, the amine monomer is preferably at least one selected from the group consisting of 2-(dimethylamino)ethyl methacrylate, 2-(dimethylamino)ethyl acrylate, 2-(diethylamino)ethyl methacrylate, 2-(diisopropylamino)ethyl methacrylate, and 2-(tert-butylamino)ethyl methacrylate, from the viewpoint of reactivity. Examples of the amine monomer include 2-(dimethylamino)ethyl methacrylate, 2-(dimethylamino)ethyl acrylate, 2-(diethylamino)ethyl methacrylate, 2-(diisopropylamino)ethyl methacrylate, and 2-(tert-butylamino)ethyl methacrylate. Among these, 2-(dimethylamino)ethyl methacrylate and 2-(diethylamino)ethyl methacrylate are more preferred from the viewpoint of reactivity.
[0020] In the antifouling member of the present invention, the hydrophilic monomer is preferably electrically neutral. In the antifouling member of the present invention, the hydrophilic monomer is preferably at least one selected from the group consisting of 2-hydroxyethyl methacrylate, N-vinyl-2-pyrrolidone, and polyethylene glycol monomethyl ether methacrylate. Examples of the hydrophilic monomer include 2-hydroxyethyl methacrylate, N-vinyl-2-pyrrolidone, polyethylene glycol monomethyl ether methacrylate, 2,3-dihydroxypropyl methacrylate, 2-hydroxyethyl acrylate, hydroxypropyl methacrylate, and 2-hydroxy-3-phenoxypropyl 2-methylpropenoate. Among these, 2-hydroxyethyl methacrylate and poly(ethylene glycol) methacrylate are more preferable from the viewpoint of low protein adsorption.
[0021] In the antifouling member of the present invention, the crosslinking agent is preferably at least one selected from the group consisting of ethylene glycol diacrylate, ethylene glycol dimethacrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, and 1,6-hexanediol diacrylate. By doing so, the gaps between the polymers can be filled, and low protein adsorption can be achieved. Examples of the crosslinking agent include ethylene glycol diacrylate, ethylene glycol dimethacrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, 1,6-hexanediol diacrylate, divinylbenzene, neopentyl glycol diacrylate, 3-methyl-1,5-pentanediol diacrylate, 1,9-nonanediol diacrylate, hydroxypivalic acid neopentyl glycol acrylic acid adduct, and 2-hydroxy-3-acryloyloxypropyl methacrylate. Among these, polyethylene glycol diacrylate and 1,6-hexanediol diacrylate are preferred from the viewpoint of low protein adsorption.
[0022] As a second structural feature, the antifouling member of the present invention preferably has a film comprising a polymer of a betaine monomer. A polymer of a betaine monomer has positive and negative charges in the molecule. Therefore, the polymer chains are attracted to each other by electrostatic interaction, and a shielding effect occurs between the chains, so that the zeta potential at pH=7 can be controlled to be between -10.0 mV and 10.0 mV. In the antifouling member of the present invention, the betaine monomer is 2-(methacryloyloxy)ethyl 2-(trimethylammonio)ethyl phosphate, 2-[[2-(methacryloyloxy)ethyl]dimethylammonio]acetic acid, 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propionate, 3-[(3-acrylamidopropyl)dimethylammonio]propanoate, 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1-sulfonic acid, 4-[[2-(methacryloyloxy)ethyl]dimethylammonio]butane-1-sulfonic acid, 3-[[2-(acryloyloxy)ethyl]dimethylammonio]propane-1-sulfonic acid, 3-[(3-methacrylamidopropyl)dimethylammonio]propane-1-sulfonic acid, 3-[(3-acrylamidopropyl)dimethylammonio]propane-1-sulfonic acid Among these, 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propionate, 2-(methacryloyloxy)ethyl 2-(trimethylammonio)ethyl phosphate, and 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1-sulfonic acid are more preferred from the viewpoint of low protein adsorption.
[0023] As a third structural feature, the antifouling member of the present invention preferably has a membrane that comprises a polymer of a betaine monomer and a polymer of a hydrophilic monomer, or a copolymer of a betaine monomer and a hydrophilic monomer. A configuration can be adopted in which a polymer of a hydrophilic monomer or a copolymer of a betaine monomer and a hydrophilic monomer is further provided on the polymer of a betaine monomer. In this way, the zeta potential at pH=7 can be controlled to be between -10.0 mV and 10.0 mV, and low protein adsorption can be achieved.
[0024] The antifouling member of the present invention preferably has a substrate made of stainless steel or glass, which allows the member to be used as a member for an in-vitro diagnostic device, as described below.
[0025] In the antifouling member of the present invention, the film preferably has a charge adjustment portion having a polarity opposite to that of the substrate and a hydrophilic portion. The charge adjustment portion and the hydrophilic portion may be in different layers or may be in the same layer. The charge adjustment portion is, for example, a portion made of a monomer having a polarity opposite to that of the substrate, or a portion made of a betaine monomer. The hydrophilic portion is, for example, a portion made of a hydrophilic monomer, or a portion made of a betaine monomer.
[0026] In addition, in the antifouling member of the present invention, it is preferable that the binding site bonded to the substrate is represented by the following formula (1-1) or formula (1-2), the charge adjustment site is a copolymer of monomers represented by the following formulas (2-1), (2-2) and (2-3) or represented by the following formula (2-4), and the hydrophilic site is represented by the following formula (3-1) or formula (3-2). [ka] [ka] [ka] [ka] [ka] [ka] [ka] [ka] (however, In formula (1-1) and formula (1-2), * represents a bonding position with the substrate, ** represents a bonding position with the charge adjustment moiety, R1 represents an alkylene group or an oxyalkylene group, R2 represents a CH=CH (vinylene group), CH=C(CH3) (isopropenylene group), HC=CH=C(=O)-O (acryloyloxy group), HC=C(CH3)-C(=O)-O (methacryloyloxy group), or HC=C(CH3)-C(=O)-NH (methacryloylamino group), and l is 1≦l≦6; In formulae (2-1), (2-2), and (2-3), R3 represents hydrogen or a methyl group, R4, R5, and R8 each independently represent an alkylene group having 1 to 6 carbon atoms, R6 represents hydrogen or an alkyl group having 1 to 3 carbon atoms, R7 represents an oxyalkylene group having 1 to 3 carbon atoms, and in formula (2-4), ** represents a bonding position with the bonding site, R9 and R10 each independently represent an alkylene group or an oxyalkylene group, and R11 represents -COO - where m is 4≦m≦1000; In formula (3-1) and formula (3-2), *** represents a bonding position with the charge adjustment portion, R8 represents an alkylene group having 1 to 6 carbon atoms, n is 4≦n≦1000, R9 and R10 each independently represent an alkylene group or an oxyalkylene group, and R11 represents —COO - where m is 4≦m≦1000.
[0027] <Method for measuring membrane zeta potential> The zeta potential of the membrane can be measured by electrophoretic light scattering using a zeta potential measurement system ELSZ-2000 (Otsuka Electronics Co., Ltd.). The membrane is attached to the top surface of a cell of a cell unit for flat plate samples (Otsuka Electronics Co., Ltd.), the cell is filled with a 10 mM sodium chloride solution at pH=7 in which monitor particles (Otsuka Electronics Co., Ltd.) are dispersed, and electrophoresis of the monitor particles is performed to measure the electrical mobility of the monitor particles. The zeta potential (mV) of the membrane at pH=7 can be calculated by analyzing the obtained data on electrical mobility using the Mori-Okamoto equation and the Smoluchowski equation.
[0028] <TOF-SIMS measurement method for films> For the detection of halogen present on the surface of the film, TOF-SIMS (manufactured by ULVAC-PHI, Inc., NanoTOF II) is used. The analysis conditions are as follows. Sample preparation: Attach the substrate on which the film is formed to an indium sheet. Sample pretreatment: None Primary ion: Bi3+ + Acceleration voltage: 30 kV Charge neutralization mode: On Measurement mode: Negative Raster size: 300 μm Integration time: 180 seconds From the ion amount obtained by performing the above measurement, the ion amount of halogen atoms / total ion amount can be determined.
[0029] <X-ray photoelectron spectroscopy (ESCA measurement) method> The measurement apparatus and measurement conditions are as follows. · Measurement apparatus: X-ray photoelectron spectrometer: Quantum2000 (manufactured by ULVAC-PHI, Inc.) · X-ray source: Monochromatic Al Kα · X-ray setting: 100 μm φ (25 W (15 KV)) · Photoelectron extraction angle: 45 degrees · Neutralization condition: Combined use of neutralization gun and ion gun · Analysis area: 300 × 200 μm · Pass Energy: 58.70 eV · Step size: 0.125 eV · Analysis software: Maltipak (PHI) During measurement, first perform qualitative analysis in the entire element range by Survey analysis, and then perform quantitative analysis by narrow scan for each detected element at the integration times shown in Table 1.
[0030]
Table 1
[0031] The quantitative values obtained in the ESCA measurement of the substrate were as follows: The amount of C atoms (atomic%) / the amount of atoms of the element X most abundant on the surface of the substrate (atomic%) is A, The quantitative values obtained in the ESCA measurement of the film on the substrate were as follows: The amount of C atoms (atomic %) / the amount of atoms of the element X (atomic %) is defined as B, and the value of B / A can be calculated.
[0032] Second Embodiment The second embodiment relates to a method for producing an antifouling member. Each component of the antifouling member is as described above, and therefore a description thereof will be omitted. The present invention also relates to a method for producing a member having a film provided on the surface of a substrate. There are three preferred examples of the production method. The first of these will be described. The first example of the method for producing an antifouling member of the present invention is a method for producing an antifouling member having a film provided on the surface of a substrate, comprising the steps of: a bonding step of bonding a hydrolysate of a silane coupling agent or a condensate of a phosphonic acid derivative to a surface of the substrate; a charge adjustment portion forming step of copolymerizing a monomer having a polarity opposite to that of the substrate, a hydrophilic monomer, and a crosslinking agent in the presence of a polymerization initiator after the bonding step; The method includes a hydrophilic portion forming step, which is performed after the charge adjustment portion forming step, of adding a hydrophilic monomer and polymerizing the monomer to form a hydrophilic portion.
[0033] The above-mentioned types of silane coupling agents can be used as the silane coupling agent. The hydrolysis of the silane coupling agent can be carried out by a known method. Although the optimal pH for hydrolysis varies depending on the type of silane coupling agent, it is preferable to select a pH at which the condensation rate is slow. For example, in the case of 3-(methacryloyloxy)propyltrimethoxysilane, it is preferable to carry out the hydrolysis in an aqueous solution of pH=4±0.5, since condensation can be suppressed. In addition, it is preferable to carry out the hydrolysis at a concentration of 0.5 wt% or more and 70.0 wt% or less. More preferably, it is 0.5 wt% or more and 5.0 wt% or less, and within this range, condensation of the hydrolyzate of the silane coupling agent can be effectively suppressed.
[0034] The bonding process of bonding the hydrolyzate of the silane coupling agent to the substrate will be described. The substrate is preferably ultrasonically cleaned using one or more types of alkali, surfactant, or organic solvent to remove organic matter adhering to the surface before use. It is also preferable to further perform UV / O3 cleaning for 1 minute to 60 minutes to remove organic matter adhering to the surface before use. The cleaned substrate is immersed for 30 seconds to 10 minutes in an aqueous solution of pH=4±0.5 in which 0.5 wt% to 5.0 wt% of the hydrolyzate of the silane coupling agent is dissolved. Thereafter, the substrate is dried for 30 seconds to 1800 seconds in an atmosphere of 10°C to 40°C. After drying, the substrate is washed with water to remove excess hydrolyzate of the silane coupling agent, and then baked in an oven at 50°C to 150°C. In this way, the hydrolyzate of the silane coupling agent is condensed on the substrate, and the bonding process is performed.
[0035] As the phosphonic acid derivative, the above-mentioned types of phosphonic acid derivatives can be used. The phosphonic acid derivative is preferably dissolved in a solvent in which the phosphonic acid derivative is soluble. Preferred solvents include alcohol, tetrahydrofuran, acetone, N-methylpyrrolidone, and dimethylformamide. More preferred are alcohol and tetrahydrofuran, which allow the bonding step with the substrate to proceed smoothly.
[0036] The bonding step of bonding the condensate of the phosphonic acid derivative to the substrate will be described. The cleaning of the substrate is preferably carried out in the same manner as the bonding step for the silane coupling agent. A solution of the phosphonic acid derivative of 0.1 mmol / l or more and 50 mmol / l or less is prepared. Any solvent that dissolves the phosphonic acid derivative may be used, and examples of the solvent include alcohol, tetrahydrofuran, acetone, toluene, N-methylpyrrolidone, and dimethylformamide. Alcohol and tetrahydrofuran are more preferable. The washed substrate is immersed in the prepared phosphonic acid derivative solution for 1 minute or more and 120 minutes or less. Then, the substrate is placed in an oven at 15°C or more and 150°C or less for 1 minute or more and 2880 minutes or less. Then, ultrasonic cleaning is performed with tetrahydrofuran and methanol to remove the multilayer film. In this manner, the condensate of the phosphonic acid derivative is bonded to the substrate.
[0037] Next, the charge adjustment portion forming step will be described. The charge adjustment portion forming step is carried out by copolymerizing a monomer having an opposite polarity to the substrate, a hydrophilic monomer, and a crosslinking agent in the presence of a polymerization initiator with the substrate on which the bonding step has been carried out. There are no particular limitations as long as the monomer can be copolymerized in a state in which the polymerization initiator coexists with the monomer, but from the viewpoint of reactivity, a method in which the monomer is copolymerized after the polymerization initiator comes into contact with the substrate on which the bonding step has been carried out is preferred.
[0038] Any method may be used for contacting the substrate on which the bonding step has been performed with the polymerization initiator, but a preferred method is to place the substrate on which the bonding step has been performed in a reaction vessel, perform nitrogen replacement, and then add a solution in which the polymerization initiator has been dissolved in a reaction solvent from which oxygen has been removed by nitrogen bubbling, and stir the solution. A preferred method is to then dissolve a monomer having polarity opposite to that of the substrate, a hydrophilic monomer, and a crosslinking agent in a reaction solvent, replace the solvent with nitrogen, and place the resulting solution in a reaction vessel containing the substrate and the polymerization initiator, and heat the solution to copolymerize the monomer. The monomer having polarity opposite to that of the substrate, the hydrophilic monomer, and the crosslinking agent can be those described above.
[0039] As the reaction solvent, water, alcohol, tetrahydrofuran, acetone, N-methylpyrrolidone, dimethylformamide, etc. can be used alone or in combination. Among these, water and alcohol are preferred from the viewpoint of the solubility of the monomer. The reaction temperature is preferably determined based on the 10-hour half-life temperature of the polymerization initiator used, and is preferably carried out at 15°C or higher and 90°C or lower from the viewpoint of the stability of the monomer used and the stability of the copolymer. More preferably, it is 40°C or higher and 80°C or lower. The reaction time (heating time) is preferably 10 minutes or higher and 1440 minutes or lower. More preferably, it is 30 minutes or higher and 600 minutes or lower.
[0040] In all of the first to third examples of the method for producing an antifouling member of the present invention, the polymerization initiator is preferably 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] n-hydrate. In addition, examples of polymerization initiators include azobisisobutyronitrile (AIBN), 2,2'-azobis[2-(2-imidazolin-2-yl)propane]dihydrochloride, and 2,2'-azobis[2-(2-imidazolin-2-yl)propane]disulfate dihydrate. dihydrate), 2,2′-Azobis(2-methylpropionamidine) dihydrochloride, 2,2′-Azobis[N-(2-carboxyethyl)-2-methylpropionamidine]n-hydrate, 2,2′-Azobis[2-(2-imidazolin-2-yl)propane], 2,2′-Azobis(1-imino-1-pyrrolidino-2-methylpropane) dihydrochloride 2,2′-Azobis(1-imino-1-pyrrolidino-2-methylpropane)dihydrochloride, 2,2′-Azobis[2-methyl-N-(2-hydroxyethyl)propionamide], 2,2′-Azobis(4-methoxy-2,4-dimethylvaleronitrile), 2,2′-Azobis(2,4-dimethylvaleronitrile), Dimethyl 2,2′-azobis(2-methylpropionate), 2,2′-Azobis(2-methylbutyronitrile)Examples of the azobis(2-methylbutyronitrile), 1,1'-azobis(cyclohexane-1-carbonitrile), 2,2'-azobis[N-(2-propenyl)-2-methylpropionamide], 1,1'-azobis(1-acetoxy-1-phenylethane), dimethyl 2,2'-azobisisobutyrate, and derivatives thereof are listed below. Among these, 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] n-hydrate is preferred from the viewpoint of reactivity.
[0041] Next, the hydrophilic portion forming step will be described. This step is a step performed after the charge adjustment portion forming step described above, and is a step of forming a hydrophilic portion by additionally polymerizing a hydrophilic monomer. As the hydrophilic monomer, the above-mentioned ones can be used. As a method of additional polymerization, the hydrophilic monomer is dissolved in a reaction solvent, and after replacing with nitrogen, it can be placed in the reaction system in which the charge adjustment portion forming step has been performed, and heated. The heating temperature can be performed in the same temperature range as the charge adjustment portion forming step, and may be the same temperature as the charge adjustment portion forming step or different. In addition, the reaction solvent described in the charge adjustment portion forming step can be used as the reaction solvent, and may be the same solvent as the charge adjustment portion forming step or different. The reaction time (heating time) is preferably 10 minutes or more and 1440 minutes or less. More preferably, it is 30 minutes or more and 600 minutes or less. As described above, it is possible to form a film on a substrate, and cleaning can be performed after the film is formed. Any method may be used as the cleaning method, but a method of performing ultrasonic cleaning using a reaction solvent is preferred.
[0042] Next, a second example of the manufacturing method will be described. The second example of the method for producing an antifouling member of the present invention is a method for producing an antifouling member having a film provided on the surface of a substrate, comprising the steps of: a bonding step of bonding a hydrolysate of a silane coupling agent or a condensate of a phosphonic acid derivative to a surface of the substrate; After the bonding step, a two-site formation step is included in which a betaine monomer is polymerized at 2.0 mg / ml or more and 12.0 mg / ml or less in the presence of a polymerization initiator to form a charge adjustment site and a hydrophilic site. Compared to the first example, this example is characterized in that after the bonding step, a betaine monomer of 2.0 mg / ml or more and 12.0 mg / ml or less is polymerized in the presence of a polymerization initiator to form a charge adjustment portion and a hydrophilic portion, thereby forming a film on the substrate. Items not described are preferably carried out in the same manner as in the first example.
[0043] As long as the polymerization initiator can polymerize the betaine monomer in the state where it coexists with the monomer, there is no particular limitation, but the method of polymerizing the betaine monomer after the polymerization initiator contacts the substrate on which the bonding process has been carried out is preferred from the viewpoint of reactivity. The method of contacting the polymerization initiator with the substrate on which the bonding process has been carried out may be any method, but the method of putting the substrate on which the bonding process has been carried out in a reaction vessel, carrying out nitrogen replacement, and then adding a solution in which the polymerization initiator has been dissolved in the reaction solvent from which oxygen has been removed by nitrogen bubbling, and stirring is preferred.
[0044] Thereafter, the betaine monomer is preferably dissolved in a reaction solvent, placed in a reaction vessel containing a substrate and a polymerization initiator, and polymerized by heating. The reaction time (heating time) is preferably 10 minutes or more and 1440 minutes or less. More preferably, it is 30 minutes or more and 600 minutes or less. The betaine monomer may be one of those mentioned above. It is also preferable to adjust the reaction solution concentration so that the betaine monomer is 2.0 mg / ml or more and 12.0 mg / ml or less during polymerization. By controlling the monomer concentration within the above range, the B / A value can be controlled to 2.0 to 5.0, making it possible to achieve both low protein adsorption and durability.
[0045] Next, a third example of the manufacturing method will be described. The third embodiment of the method for producing an antifouling member of the present invention is a method for producing an antifouling member having a film provided on the surface of a substrate, comprising the steps of: a bonding step of bonding a hydrolysate of a silane coupling agent or a condensate of a phosphonic acid derivative to a surface of the substrate; a charge adjustment portion forming step of polymerizing the betaine monomer in the presence of a polymerization initiator after the bonding step; The method includes a hydrophilic portion forming step, which is performed after the charge adjustment portion forming step, of adding a hydrophilic monomer and polymerizing the monomer to form a hydrophilic portion.
[0046] Compared to the second example, it is characterized in that after the bonding step, a charge adjustment part formation step is performed in which a betaine monomer is polymerized in the presence of a polymerization initiator, and after the charge adjustment part formation step, a hydrophilic monomer is added and polymerized to form a hydrophilic part. Items not described are preferably performed in the same manner as in the first example.
[0047] There is no particular limitation as long as the betaine monomer can be polymerized in a state where the polymerization initiator coexists with the monomer, but a method in which the polymerization initiator contacts the substrate on which the bonding process has been performed and then polymerizes the betaine monomer is preferred from the viewpoint of reactivity. Any method may be used as a method for contacting the substrate on which the bonding process has been performed with the polymerization initiator, but a method in which the substrate on which the bonding process has been performed is placed in a reaction vessel, nitrogen replacement is performed, and then a solution in which the polymerization initiator is dissolved in a reaction solvent from which oxygen has been removed by nitrogen bubbling is placed and stirred is preferred. Thereafter, a method in which the betaine monomer is dissolved in a reaction solvent, placed in a reaction vessel containing the substrate and the polymerization initiator, and polymerized by heating is preferred. The betaine monomer can be one of those mentioned above. The reaction time (heating time) is preferably 10 minutes or more and 1440 minutes or less. More preferably, it is 30 minutes or more and 600 minutes or less. In this way, the charge adjustment portion formation process is carried out.
[0048] After the charge adjustment portion forming step, a hydrophilic monomer is added and polymerized to form a hydrophilic portion. The hydrophilic portion can be formed by the same method as in the first example.
[0049] In the present invention, the substrate preferably includes stainless steel or glass. Since hydroxyl groups exist on the outermost surfaces of stainless steel and glass, the hydrolyzate of the silane coupling agent or the phosphonic acid derivative can condense to form a covalent bond. As a result, it is preferable because good durability can be imparted.
[0050] In the present invention, the binding site that binds to the base material is preferably represented by formula (1-1) or formula (1-2). [ka] [ka] In formula (1-1) and formula (1-2), * represents a bonding position with the substrate, ** represents a bonding position with the charge adjustment moiety, R1 represents an alkylene group or an oxyalkylene group, R2 represents CH=CH (vinylene group), CH=C(CH3) (isopropenylene group), It represents any one of HC=CH=C(=O)-O (acryloyloxy group), HC=C(CH3)-C(=O)-O (methacryloyloxy group), and HC=C(CH3)-C(=O)-NH (methacryloylamino group), where l is 1≦l≦6.
[0051] The charge adjustment portion is preferably a copolymer of monomers represented by formula (2-1), formula (2-2) and formula (2-3), or is preferably represented by formula (2-4). [ka] [ka] [ka] [ka] In formulae (2-1), (2-2), and (2-3), R3 represents hydrogen or a methyl group, R4, R5, and R8 each independently represent an alkylene group having 1 to 6 carbon atoms, R6 represents hydrogen or an alkyl group having 1 to 3 carbon atoms, R7 represents an oxyalkylene group having 1 to 3 carbon atoms, and in formula (2-4), ** represents a bonding position with the bonding site, R9 and R10 each independently represent an alkylene group or an oxyalkylene group, and R11 represents -COO - where m is 4≦m≦1000.
[0052] The hydrophilic portion is preferably represented by formula (3-1) or formula (3-2). [ka] [ka] In formula (3-1) and formula (3-2), *** represents a bonding position with the charge adjustment portion, R8 represents an alkylene group having 1 to 6 carbon atoms, n is 4≦n≦1000, R9 and R10 each independently represent an alkylene group or an oxyalkylene group, and R11 represents —COO - wherein m is 4≦m≦1000.
[0053] The membrane of the present invention preferably has a dry thickness of 1 nm or more and 200 nm or less. More preferably, it is 1 nm or more and less than 10 nm. The membrane thickness may be measured by any method, but can be measured by an ellipsometer or the like. By having the membrane thickness in the above range, it is possible to achieve both low protein adsorption and durability.
[0054] [Application example] The application examples of the present invention are related to in vitro diagnostic device components. The in vitro diagnostic device components of the present invention preferably use the above-mentioned antifouling material. Below, as examples of in vitro diagnostic device components, a sample testing and analysis cell and a tip of a pipette are given, but the application examples of the present invention are not limited to these two uses. (Sample testing and analysis cell) The specimen testing and analysis cell has a rectangular cylindrical shape. Fig. 1 is a perspective view of a specimen testing and analysis cell according to an application of the present invention. As shown in Fig. 1, the specimen testing and analysis cell is a glass container having a bottom and four side faces, and has a mouth 11 (opening) on the side opposite to the bottom face 12.
[0055] FIG. 2 is a top view of a specimen inspection and analysis cell according to an application example of the present invention. The specimen inspection and analysis cell has a first optical path surface on which the analytical light is incident and a second optical path surface opposite to the first optical path surface. Specifically, as shown in FIG. 2, the four side surfaces include a first optical path surface 21 on which the analytical light 25 is incident, and a second optical path surface 22 opposite to the first optical path surface 21 and on which the analytical light 26 is emitted, and a non-optical path surface 23 through which the analytical light does not pass, and a non-optical path surface 24 opposite to the non-optical path surface 23. Although the two optical path surfaces are distinguished as the first optical path surface 21 and the second optical path surface 22, this is only for the sake of explanation, and the functions and materials of the first optical path surface 21 and the second optical path surface 22 are similar. In FIG. 2, a rectangular cylindrical specimen inspection and analysis cell is shown as an example, but a cylindrical shape may also be used.
[0056] The size of the specimen testing and analysis cell is not particularly limited. As an example, the inner dimensions of the surface parallel to the bottom are 4 mm x 5 mm, the outer dimensions are 6 mm x 7 mm, and the overall height (the distance from the opening to the outer bottom surface) is 40 mm. There is no problem if the inner diameter or outer diameter is larger or smaller than this, but in recent years, there has been a demand for measurements using a small amount of sample to reduce the burden on patients, and there is a tendency for specimen testing and analysis cells to become smaller. The shape and size of the specimen testing and analysis cell are merely examples and are not limited to the above. The outer surface of the cell may be chamfered or rounded, and if the inner surface is a square tube, the inner surface may be rounded.
[0057] The specimen inspection and analysis cell is made of borosilicate glass. As the material for the specimen inspection and analysis cell, a glass material having high transmittance and excellent mechanical strength and chemical durability can be used. In the cleaning process of the specimen inspection and analysis cell in the specimen inspection and analysis device, an acidic or alkaline cleaning agent is generally used to remove dirt such as protein, and if it is assumed to be used repeatedly, it will be exposed to an acid or alkaline environment for a long period of time. In the case of resin, since it has inferior chemical durability compared to glass-based materials, the surface composition of the inner surface of the specimen inspection and analysis cell is easily modified, and the wettability of water may change over time. Examples of materials having excellent durability against acids and alkalis include quartz glass and borosilicate glass.
[0058] In this way, when the specimen testing and analysis cell is made of glass, the antifouling member of the present invention can be applied to the specimen testing and analysis cell. Through absorbance measurement using the specimen testing and analysis cell, the concentration of the target substance (biological substance such as protein or ion) can be detected with high accuracy.
[0059] (Pipette tip) The tip of the pipette refers to the tip of the pipette tip when the pipette has a pipette tip, and refers to the tip of the syringe when the pipette does not have a pipette tip. At least the tip of the pipette is conductive. The tip of the pipette is electrically connected to a measuring unit for electrical characteristics. The pipette can quantitatively suck and discharge liquid by the reciprocating motion of the plunger. This allows the pipette to provide liquid to a flow path and collect liquid from the flow path. From the viewpoint of preventing the inclusion of impurities, it is preferable that the pipette tip is replaceable.
[0060] The material of the pipette is not particularly limited. Examples of the material of the pipette include resin and glass. Polypropylene is usually used as the material of the pipette. The method of imparting conductivity to the tip of the pipette is not particularly limited, and for example, the pipette tip made of resin may contain an additive for imparting conductivity, or may contain a conductive part made of metal. Examples of additives for imparting conductivity include carbon-based additives made of conductive carbon such as carbon fiber and carbon black; and metal-based additives in which metal is coated on fibers, powders, glass fibers, etc.
[0061] In this way, when the tip of a pipette contains a metal, the antifouling member of the present invention can be applied to the tip of the pipette. When the tip of a pipette contains a metal, for example, it is possible to measure the presence or amount of a substance to be detected (such as a protein or DNA) with high accuracy by using surface plasmon resonance.
[0062] (Dispensing probe) The dispensing probe is in the form of a thin tube, and the sample dispensing probe aspirates a sample from a sample container and dispenses it into a reaction container, while the reagent dispensing probe aspirates a reagent from a reagent container and dispenses it into a reaction container. The material of the dispensing probe is not particularly limited, but examples of the material include stainless steel, glass, or titanium. In this case, the antifouling member of the present invention can be applied to the dispensing probe. EXAMPLES
[0063] The present invention will be described in detail with reference to the following examples. However, the present invention is not limited to these examples. In the examples and comparative examples, "parts" and "%" are all by mass unless otherwise specified.
[0064] Example 1 A slide glass (S1111) manufactured by Matsunami Glass Industry was placed in a tall beaker containing 1M sodium hydroxide solution, ultrasonically cleaned, and then washed with water. 3-(methacryloyloxy)propyltrimethoxysilane was diluted to 1% by mass with dilute hydrochloric acid (pH = 4) and stirred for 1 hour to carry out hydrolysis. The hydrolysis liquid was placed in a tall beaker, and a slide glass that had been cleaned and then UV / O3 cleaned for 15 minutes was immersed in the hydrolysis liquid for 1 minute, removed, and dried at 30°C for 5 minutes. The slide glass was washed with pure water to remove excess hydrolyzate, and then placed in an oven at 90°C and baked for 60 minutes to carry out a condensation reaction.
[0065] The slide glass after the condensation reaction was placed in a 300 ml glass container and the lid was closed. The inside of the glass container was replaced with nitrogen, and ultrapure water was placed in a 100 ml glass container while flowing nitrogen at 200 ml / min. A needle was placed in the ultrapure water in the glass container, and nitrogen was bubbled at 150 ml / min for 30 minutes. As a polymerization initiator, 126 mg of 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine]n-hydrate was dissolved in 20 ml of ultrapure water replaced with nitrogen, and placed in a 300 ml glass container. The mixture was then stirred at room temperature for 60 minutes. As a betaine monomer, 900 mg of 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propionate was dissolved in 30 ml of ultrapure water replaced with nitrogen, and placed in a 300 ml glass container. The polymerization reaction was then carried out at 60°C for 4 hours. Thereafter, the slide glass after the polymerization reaction was washed with RO water and ultrasonically cleaned at 28 kHz to obtain a slide glass having a film. The obtained slide glass having the film was subjected to the measurement of zeta potential, TOF-SIMS measurement, and ESCA measurement by the above-mentioned method, and was also evaluated for low protein adsorption and durability by the following method.
[0066] <Low protein adsorption> 400 mm per well on the membrane-bearing slide 2 Attach the slide and chamber (2 wells) separated by a separator. Dissolve bovine serum albumin (BSA) to 50 ppm in acetate buffer (pH = 4.8) with an ionic strength of 0.001 (BSA solution). Dilute the 50 ppm BSA solution with acetate buffer to prepare 40 ppm, 25 ppm, and 0 ppm calibration curve samples. Add 150 μl of 50 ppm BSA solution to each well, cover with parafilm, and incubate at 37° C. for 30 minutes. Solution A and solution B of a protein assay BCA kit (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) are mixed at a ratio of 50 / 1 (BCA solution), and 400 μl of the solution is placed in a 1.5 ml sample tube. After incubation, a 90 μl sample is removed from the well and placed into the sample tube containing the BCA solution. Add 90 μl of each of the calibration curve samples (50 ppm, 40 ppm, 25 ppm, 0 ppm) to 1.5 ml sample tubes containing 400 μl of BCA solution prepared separately. After stirring each sample tube, centrifuge it to remove any liquid adhering to the lid. Thereafter, the mixture is kept at 60°C for 30 minutes to allow the color reaction to occur. After the color reaction, 150 μl of each sample is placed in a 96-well plate (n=3), and the absorbance at 562 nm is measured. Calculate the average absorbance value for n=3. Create a calibration curve from the average absorbance values of the calibration curve samples. The BSA solution concentration of the membrane sample is calculated from the calibration curve, and the amount of BSA adsorbed to the membrane (μg) is calculated from the change from 50 ppm. The calculated amount of BSA adsorbed was calculated based on the area per well (400 mm 2 ) to obtain the amount of BSA adsorbed per unit area (μg / cm 2 ) was calculated and the amount of BSA adsorbed to the slide glass was 0.6 μg / cm 2 The protein adsorption rate was calculated by dividing the total amount by the value of the total amount of BSA adsorbed onto the slide glass, which was calculated in advance for n=15 or more samples. A protein adsorption rate calculated in this manner of 15% or less is sufficient for the low protein adsorption (low protein adsorption) of the present invention. If the calculated protein adsorption rate is 15% or less, there is no influence on the decrease in detection sensitivity or reproducibility due to protein adhesion.
[0067] <Durability> An alkaline detergent (Maxpia (registered trademark) B14 (Canon Medical Systems Corporation)) was diluted 76 times with ultrapure water to make 150 ml. The 76-fold diluted MaxpiaB14 and the slide glass having the membrane were placed in a 300-ml flat-bottom container and stirred for 3 hours. After 3 hours, the slides were removed and washed with water. Thereafter, an evaluation of "low protein adsorption" was carried out, and the protein adsorption rate was calculated. A durability (protein adsorption rate after washing with water) of 25% or less is sufficient for the present invention. If the durability (protein adsorption rate after washing with water) is 25% or less, alkali resistance can be effectively exhibited.
[0068] Example 2 The steps up to the condensation reaction were carried out in the same manner as in Example 1. The slide glass after the condensation reaction was placed in a 300 ml glass container and the lid was closed. The atmosphere in the glass container was replaced with nitrogen, and 65 ml of ultrapure water and 35 ml of ethanol were placed in the glass container while flowing nitrogen at 200 ml / min. A needle was placed in the liquid in the glass container, and nitrogen was bubbled at 150 ml / min for 30 minutes. As a polymerization initiator, 126 mg of 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] n-hydrate was dissolved in 20 ml of ultrapure water replaced with nitrogen, and the solution was placed in a 300 ml glass container. The mixture was then stirred at room temperature for 60 minutes. 900 mg of 2-hydroxyethyl methacrylate as a hydrophilic monomer, 100 mg of 2-(dimethylamino)ethyl methacrylate as a monomer having the opposite polarity to the substrate, and 30 mg of polyethylene glycol diacrylate (n = about 9) as a crosslinking agent were dissolved in a mixed solvent of ultrapure water / ethanol = 10 ml / 15 ml substituted with nitrogen, and then placed in a 300 ml glass container. Then, a polymerization reaction was carried out at 60 ° C for 3 hours. Furthermore, 1000 mg of 2-hydroxyethyl methacrylate as an additional hydrophilic monomer was dissolved in a mixed solvent of ultrapure water / ethanol = 7 ml / 7 ml substituted with nitrogen, and then placed in a 300 ml glass container, and a polymerization reaction was carried out at 60 ° C for 3 hours. Then, the slide glass after the polymerization reaction was washed with ethanol and RO water and ultrasonically cleaned at 28 kHz to obtain a slide glass having a film. The obtained slide glass was subjected to zeta potential measurement, TOF-SIMS measurement, and ESCA measurement. In addition, low protein adsorption and durability were evaluated in the same manner as in Example 1.
[0069] (Examples 3, 5, 6, and 14) The same procedures as in Example 1 were carried out up to the evaluation stage, except that the betaine monomer was changed as shown in Table 2.
[0070] [Table 2]
[0071] (Examples 4, 9, 11, 12, and 15) Except for changing the various materials as shown in Table 3, the same procedures as in Example 2 were carried out up to the evaluation.
[0072] [Table 3]
[0073] In Table 3, VA-57 represents 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] n-hydrate, V50 represents 2,2'-azobis(2-methylpropionamidine) dihydrochloride, HEMA represents 2-hydroxyethyl methacrylate, CBMA represents 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propionate, DMAEM represents 2-(dimethylamino)ethyl methacrylate, DEAEM represents 2-(diethylamino)ethyl methacrylate, EG (n=9) represents polyethylene glycol diacrylate (n=approximately 9), and HDDA represents 1,6-hexanediol diacrylate.
[0074] Example 7 The steps up to the condensation reaction were carried out in the same manner as in Example 1. The slide glass after the condensation reaction was placed in a 300 ml glass container and the lid was closed. The inside of the glass container was replaced with nitrogen, and 50 ml of ultrapure water and 50 ml of ethanol were placed in the glass container while flowing nitrogen at 200 ml / min. A needle was placed in the liquid in the glass container, and nitrogen was bubbled at 150 ml / min for 30 minutes. As a polymerization initiator, 126 mg of 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine]n-hydrate was dissolved in 20 ml of ultrapure water replaced with nitrogen, and placed in a 300 ml glass container. The mixture was then stirred at room temperature for 60 minutes. As a betaine monomer, 360 mg of 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propionate was dissolved in 30 ml of ultrapure water replaced with nitrogen, and placed in a 300 ml glass container. The polymerization reaction was then carried out at 60°C for 3 hours. Furthermore, 720 mg of 2-hydroxyethyl methacrylate was dissolved in 15 ml of ultrapure water substituted with nitrogen as a hydrophilic monomer to be added, and the solution was poured into a 300 ml glass container and polymerized at 60° C. for 3 hours. After that, the slide glass after the polymerization reaction was washed with ethanol and RO water and ultrasonically cleaned at 28 kHz to obtain a slide glass having a film. The obtained slide glass was subjected to zeta potential measurement, TOF-SIMS measurement, and ESCA measurement. In addition, low protein adsorption and durability were evaluated in the same manner as in Example 1.
[0075] Example 8 The same procedure as in Example 7 was repeated up to the evaluation, except that the betaine monomer was changed to 450 mg of 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propionate and the additional hydrophilic monomer was changed to 900 mg of polyethylene glycol monomethyl ether methacrylate (AVERAGE Mn 950).
[0076] Example 10 A slide glass (S1111) manufactured by Matsunami Glass Industry was placed in a tall beaker containing 1M sodium hydroxide solution and ultrasonically cleaned. 2-Methacryloyloxyethyl acid phosphate was diluted to 0.5% by mass with tetrahydrofuran and placed in a tall beaker. The slide glass, which had been ultrasonically cleaned and then UV / O3 cleaned for 15 minutes, was immersed in the solution for 60 minutes, removed, and dried at 30°C for 5 minutes. The slide glass was washed with tetrahydrofuran and baked in an oven at 120°C for 60 minutes to carry out a condensation reaction.
[0077] The slide glass after the condensation reaction was placed in a 300 ml glass container and the lid was closed. The glass container was replaced with nitrogen, and ultrapure water was placed in a 100 ml glass container while flowing nitrogen at 200 ml / min. A needle was placed in the ultrapure water in the glass container, and nitrogen was bubbled at 150 ml / min for 30 minutes. As a polymerization initiator, 126 mg of 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine]n-hydrate was dissolved in 20 ml of ultrapure water replaced with nitrogen, and placed in a 300 ml glass container. The mixture was then stirred at room temperature for 60 minutes. As a betaine monomer, 630 mg of 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propionate was dissolved in 30 ml of ultrapure water replaced with nitrogen, and placed in a 300 ml glass container. The polymerization reaction was then carried out at 60°C for 4 hours. Thereafter, the slide glass after the polymerization reaction was washed with RO water and ultrasonically cleaned at 28 kHz to obtain a slide glass having a film. The obtained slide glass having the film was subjected to the measurement of zeta potential, TOF-SIMS measurement, and ESCA measurement by the above-mentioned method, and was also evaluated for low protein adsorption and durability by the following method.
[0078] (Example 13) The procedures up to the condensation reaction were the same as in Example 1. The slide glass after the condensation reaction was placed in a 300 ml glass container and the lid was closed. The inside of the glass container was replaced with nitrogen, and 50 ml of ultrapure water and 20 ml of ethanol were placed in the glass container while flowing nitrogen at 200 ml / min. A needle was inserted into the liquid in the glass container, and nitrogen was bubbled at 150 ml / min for 30 minutes. As a polymerization initiator, 50 mg of 2,2'-azobis(isobutyronitrile) was dissolved in 50 ml of nitrogen-substituted ethanol and placed in a 300 ml glass container. The mixture was then stirred at room temperature for 60 minutes. As a betaine monomer, 900 mg of 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propionate was dissolved in 30 ml of nitrogen-substituted ultrapure water and placed in a 300 ml glass container. The polymerization reaction was then carried out at 60°C for 4 hours. Thereafter, the slide glass after the polymerization reaction was spray-washed with ethanol and RO water and ultrasonically cleaned at 28 kHz to obtain a slide glass having a film. The obtained slide glass was subjected to zeta potential measurement, TOF-SIMS measurement, and ESCA measurement. In addition, low protein adsorption and durability were evaluated in the same manner as in Example 1.
[0079] Example 16 The procedure from preparation to evaluation was the same as in Example 1, except that the slide glass (S1111) manufactured by Matsunami Glass Industry was changed to a SUS304 plate (width×length×thickness=26×60×1 mm).
[0080] (Example 17) The process from preparation to evaluation was carried out in the same manner as in Example 2, except that the slide glass (S1111) manufactured by Matsunami Glass Industry was changed to a SUS304 plate (width×length×thickness=26×60×1 mm).
[0081] Comparative Example 1 A slide glass (S1111) manufactured by Matsunami Glass Industry Co., Ltd. was placed in a tall beaker containing 1M sodium hydroxide solution, ultrasonically cleaned, and then rinsed with water. It was then subjected to UV / O3 cleaning for 15 minutes. Lipidure-S (NOF Corporation) was diluted to 1% by mass with toluene and placed in a tall beaker. The slide glass after UV / O3 cleaning was immersed in it for 1 minute, then removed and dried at 30°C for 24 hours to form a film. The slide glass on which the film was formed was subjected to zeta potential measurement, TOF-SIMS measurement, and ESCA measurement in the same manner as in Example 1. In addition, the low protein adsorption property and durability were evaluated.
[0082] Comparative Example 2 The same procedures as in Example 2 were repeated up to the evaluation, except that the hydrophilic monomer was changed to 800 mg of 2-hydroxyethyl methacrylate, and the monomer having the opposite polarity to the substrate was changed to 200 mg of 2-(dimethylamino)ethyl methacrylate.
[0083] Comparative Example 3 The steps up to the condensation reaction were carried out in the same manner as in Example 1. The slide glass after the condensation reaction was placed in a 300 ml glass container and the lid was closed. The inside of the glass container was replaced with nitrogen, and 65 ml of ultrapure water and 35 ml of ethanol were placed in the glass container while flowing nitrogen at 200 ml / min. A needle was placed in the liquid in the glass container, and nitrogen was bubbled at 150 ml / min for 30 minutes. As a polymerization initiator, 126 mg of 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] n-hydrate was dissolved in 20 ml of ultrapure water replaced with nitrogen, and placed in a 300 ml glass container. The mixture was then stirred at room temperature for 60 minutes. As a hydrophilic monomer, 900 mg of 2-hydroxyethyl methacrylate was dissolved in a mixed solvent of ultrapure water replaced with nitrogen / ethanol = 10 ml / 15 ml, and placed in a 300 ml glass container. The polymerization reaction was then carried out at 60 °C for 6 hours. Thereafter, the slide glass after the polymerization reaction was spray-washed with ethanol and RO water and ultrasonically cleaned at 28 kHz to obtain a slide glass having a film. The obtained slide glass was subjected to zeta potential measurement, TOF-SIMS measurement, and ESCA measurement. In addition, low protein adsorption and durability were evaluated in the same manner as in Example 1.
[0084] Comparative Example 4 A slide glass (S1111) manufactured by Matsunami Glass Industry Co., Ltd. was placed in a tall beaker containing 1M sodium hydroxide solution, ultrasonically cleaned, and then rinsed with water. It was then subjected to UV / O3 cleaning for 15 minutes. LAMBIC-1000W (Osaka Organic Chemical Industry Co., Ltd.) was diluted 5-fold with ultrapure water and placed in a tall beaker. A slide glass that had been cleaned with UV / O3 was immersed in the solution for 1 minute, then removed and dried at 80°C for 15 minutes to form a film. The slide glass on which the film was formed was subjected to zeta potential measurement, TOF-SIMS measurement, and ESCA measurement in the same manner as in Example 1. In addition, the low protein adsorption property and durability were evaluated.
[0085] Comparative Example 5 A slide glass (S1111) manufactured by Matsunami Glass Industry Co., Ltd. was placed in a tall beaker containing 1M sodium hydroxide solution, ultrasonically cleaned, and then rinsed with water. It was then subjected to UV / O3 cleaning for 15 minutes. The cleaned slide glass was placed in a vacuum desiccator containing 10 drops of (3-aminopropyl)triethoxysilane. The pressure in the system was reduced to less than 1 mbar, and the system was isolated from the pump and placed under reduced pressure for 30 minutes. The slide glass was then baked at 110°C for 30 minutes under normal pressure. The baked slide glass was placed in a reaction vessel, which was substituted with nitrogen, and 50 ml of dehydrated tetrahydrofuran, 1.3 ml of 2-bromoisobutyryl bromide, and 1.5 ml of triethylamine were added to the reaction vessel and stirred for 1 hour. The slide glass was removed from the reaction vessel, washed with tetrahydrofuran, methanol, and ultrapure water, and dried.
[0086] The dried slide glass and 143 mg of copper (I) bromide were placed in a reaction vessel and purged with nitrogen. 156 mg of 2,2'-bipyridyl and 874 mg of 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propionate were placed in a pear-shaped flask, and after purging with nitrogen, 5 ml of nitrogen-purged methanol and 5 ml of nitrogen-purged ultrapure water were added to the pear-shaped flask and dissolved. The solution in the pear-shaped flask was added to the reaction vessel containing the slide glass and copper (I) bromide using a syringe and stirred for 1 hour. After that, it was washed with ethanol, PBS (phosphate buffered saline), and ultrapure water to obtain a slide glass with a polymer brush formed thereon. The slide glass on which the obtained polymer brush was formed was subjected to zeta potential measurement, TOF-SIMS measurement, and ESCA measurement. In addition, the low protein adsorption property and durability were evaluated in the same manner as in Example 1.
[0087] Comparative Example 6 The same procedures as in Example 1 were repeated up to the evaluation, except that the amount of 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propionate was changed to 270 mg.
[0088] Comparative Example 7 The steps up to the condensation reaction were carried out in the same manner as in Example 1. The slide glass after the condensation reaction was placed in a 300 ml glass container and the lid was closed. The atmosphere in the glass container was replaced with nitrogen, and 65 ml of ultrapure water and 35 ml of ethanol were placed in the glass container while flowing nitrogen at 200 ml / min. A needle was placed in the liquid in the glass container, and nitrogen was bubbled at 150 ml / min for 30 minutes. As a polymerization initiator, 126 mg of 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] n-hydrate was dissolved in 20 ml of ultrapure water replaced with nitrogen, and the solution was placed in a 300 ml glass container. The mixture was then stirred at room temperature for 60 minutes. 900 mg of 2-hydroxyethyl methacrylate as a hydrophilic monomer, 100 mg of 2-(dimethylamino)ethyl methacrylate as a monomer having the opposite polarity to the substrate, and 30 mg of polyethylene glycol diacrylate (n = approx. 9) as a crosslinking agent were dissolved in a nitrogen-substituted ultrapure water / ethanol = 10 ml / 15 ml mixed solvent and placed in a 300 ml glass container. Then, a polymerization reaction was carried out at 60 ° C for 3 hours. After the polymerization reaction, the slide glass was washed with ethanol and RO water and ultrasonically cleaned at 28 kHz to obtain a slide glass with a membrane. The obtained slide glass was subjected to zeta potential measurement, TOF-SIMS measurement, and ESCA measurement. In addition, low protein adsorption and durability were evaluated in the same manner as in Example 1.
[0089] Comparative Example 8 The surface of a SUS304 plate (width x length x thickness = 26 x 60 x 1 mm) was washed with acetone and dried. It was immersed in a 2% by mass aqueous solution of 3-(acryloyloxy)propyltrimethoxysilane (with 2% by mass of acetic acid added) for 10 minutes, removed, and dried at 40°C for 24 hours. It was then washed with water and then washed with acetone. This treated SUS304 plate was immersed in a 1.5% by mass ethanol solution of azobisisobutyronitrile for 5 minutes, removed, and dried. This SUS304 plate was placed in a glass container containing a 1.25 M aqueous solution of 3-sulfopropyl methacrylate potassium salt, and the container was closed with a lid. After introducing nitrogen gas to replace the atmosphere, the glass container was heated in a water bath at 60°C for 5 hours to polymerize. The surface was then washed with water to wash away unreacted monomers, etc., to obtain a SUS304 plate having a membrane. The obtained SUS304 plate having a membrane was subjected to zeta potential measurement, TOF-SIMS measurement, ESCA measurement, and evaluation of low protein adsorption and durability in the same manner as in Example 1.
[0090] Comparative Example 9 The same procedures as in Example 1 were repeated up to the evaluation, except that the amount of 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propionate was changed to 180 mg. Table 4 shows the physical properties and evaluation results of the films obtained in Examples 1 to 17 and Comparative Examples 1 to 9.
[0091] [Table 4]
[0092] Disclosure of the embodiments according to the present invention includes the following configurations and methods. (Configuration 1) An antifouling member having a film provided on a substrate, the film has a condensate of a hydrolyzate of a silane coupling agent or a condensate of a phosphonic acid derivative, The film does not contain halogen atoms, The zeta potential of the membrane is -10.0 mV or more and 10.0 mV or less in water at pH=7; An antifouling member, in which, when the amount of C atoms (atomic %) in an X-ray photoelectron spectroscopy analysis (ESCA measurement) of the substrate is divided by the amount of atoms of the element X that is most abundant on the surface of the substrate (atomic %), A is taken as A, and when the amount of C atoms (atomic %) in an X-ray photoelectron spectroscopy analysis (ESCA measurement) of the film on the substrate is divided by the amount of C atoms (atomic %) (atomic %), B is taken as B / A, the value of B / A is 2.0 or more and 5.0 or less. (Configuration 2) 2. The stain-resistant member according to claim 1, wherein the film comprises a copolymer of a monomer having a polarity opposite to that of the substrate, a hydrophilic monomer, and a crosslinking agent. (Configuration 3) 2. The stain-resistant member according to claim 1, wherein the film comprises a polymer of a betaine monomer. (Configuration 4) 2. The stain-resistant member according to embodiment 1, wherein the film comprises a polymer of a betaine monomer and a polymer of a hydrophilic monomer. (Configuration 5) 5. The stain-resistant member according to configuration 2 or 4, wherein the hydrophilic monomer is electrically neutral. (Configuration 6) 5. The stain-resistant member according to configuration 2 or 4, wherein the hydrophilic monomer is at least one selected from the group consisting of 2-hydroxyethyl methacrylate, N-vinyl-2-pyrrolidone, and polyethylene glycol monomethyl ether methacrylate. (Configuration 7) The betaine monomer may be selected from the group consisting of 2-(methacryloyloxy)ethyl 2-(trimethylammonio)ethyl phosphate, 2-[[2-(methacryloyloxy)ethyl]dimethylammonio]acetate, 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propionate, 3-[(3-acrylamidopropyl)dimethylammonio]propanoate, 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1-sulfonate, 4- The antifouling member according to embodiment 3 or 4, which is at least one selected from the group consisting of [[2-(methacryloyloxy)ethyl]dimethylammonio]butane-1-sulfonic acid, 3-[[2-(acryloyloxy)ethyl]dimethylammonio]propane-1-sulfonic acid, 3-[(3-methacrylamidopropyl)dimethylammonio]propane-1-sulfonic acid, and 3-[(3-acrylamidopropyl)dimethylammonio]propane-1-sulfonic acid. (Configuration 8) the silane coupling agent is at least one selected from the group consisting of 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, 3-(methacryloyloxy)propyltriethoxysilane, 3-(methacryloyloxy)propyltriethoxysilane, vinyltrimethoxysilane, triethoxyvinylsilane, allyltrimethoxysilane, allyltriethoxysilane, and (triethoxysilyl)methyl methacrylate; The antifouling member according to any one of configurations 1 to 7, wherein the phosphonic acid derivative is at least one selected from the group consisting of 2-methacryloyloxyethyl acid phosphate, 2-acryloyloxyethyl acid phosphate, 2-(methacryloyloxy)ethyl phosphate, and acid phosphoxy polyethylene glycol monomethacrylate. (Configuration 9) 3. The stain-resistant member according to configuration 2, wherein the monomer having a polarity opposite to that of the substrate is an amine monomer. (Configuration 10) The stain-resistant member according to aspect 9, wherein the amine monomer is at least one selected from the group consisting of 2-(dimethylamino)ethyl methacrylate, 2-(dimethylamino)ethyl acrylate, 2-(diethylamino)ethyl methacrylate, 2-(diisopropylamino)ethyl methacrylate, and 2-(tert-butylamino)ethyl methacrylate. (Configuration 11) 3. The stain-resistant member according to configuration 2, wherein the crosslinking agent is at least one selected from the group consisting of ethylene glycol diacrylate, ethylene glycol dimethacrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, and 1,6-hexanediol diacrylate. (Configuration 12) 12. The stain-resistant member according to any one of configurations 1 to 11, wherein the material of the substrate is stainless steel or glass. (Configuration 13) 13. The stain-resistant member according to any one of configurations 1 to 12, wherein the film has a charge adjusting portion having a polarity opposite to that of the substrate and a hydrophilic portion. (Configuration 14) The binding site that binds to the substrate is represented by the following formula (1-1) or the following formula (1-2), The charge adjustment portion is a copolymer of monomers represented by the following formula (2-1), (2-2) and (2-3), or is represented by the following formula (2-4): 14. The stain-resistant member according to embodiment 13, wherein the hydrophilic portion is represented by the following formula (3-1) or (3-2): [ka] [ka] [ka] [ka] [ka] [ka] [ka] [ka] (however, In formula (1-1) and formula (1-2), * represents a bonding position with the substrate, ** represents a bonding position with the charge adjustment moiety, R1 represents an alkylene group or an oxyalkylene group, R2 represents a CH=CH (vinylene group), CH=C(CH3) (isopropenylene group), HC=CH=C(=O)-O (acryloyloxy group), HC=C(CH3)-C(=O)-O (methacryloyloxy group), or HC=C(CH3)-C(=O)-NH (methacryloylamino group), and l is 1≦l≦6; In formulae (2-1), (2-2), and (2-3), R3 represents hydrogen or a methyl group, R4, R5, and R8 each independently represent an alkylene group having 1 to 6 carbon atoms, R6 represents hydrogen or an alkyl group having 1 to 3 carbon atoms, R7 represents an oxyalkylene group having 1 to 3 carbon atoms, and in formula (2-4), ** represents a bonding position with the bonding site, R9 and R10 each independently represent an alkylene group or an oxyalkylene group, and R11 represents -COO - where m is 4≦m≦1000; In formula (3-1) and formula (3-2), *** represents a bonding position with the charge adjustment portion, R8 represents an alkylene group having 1 to 6 carbon atoms, n is 4≦n≦1000, R9 and R10 each independently represent an alkylene group or an oxyalkylene group, and R11 represents —COO - where m is 4≦m≦1000. (Configuration 15) A member for in-vitro diagnostic devices, using the antifouling member according to any one of configurations 1 to 14. (Method 1) A method for producing an antifouling member having a film provided on a surface of a substrate, comprising the steps of: a bonding step of bonding a hydrolysate of a silane coupling agent or a condensate of a phosphonic acid derivative to a surface of the substrate; a charge adjustment portion forming step of copolymerizing a monomer having a polarity opposite to that of the substrate, a hydrophilic monomer, and a crosslinking agent in the presence of a polymerization initiator after the bonding step; A method for producing an antifouling member, comprising: a hydrophilic portion forming step of forming a hydrophilic portion by adding a hydrophilic monomer and polymerizing the monomer after the charge adjustment portion forming step, (Method 2) A method for producing an antifouling member having a film provided on a surface of a substrate, comprising the steps of: a bonding step of bonding a hydrolysate of a silane coupling agent or a condensate of a phosphonic acid derivative to a surface of the substrate; A method for producing an antifouling member, comprising: after the bonding step, a two-site formation step of polymerizing a betaine monomer at 2.0 mg / ml or more and 12.0 mg / ml or less in the presence of a polymerization initiator to form a charge adjustment site and a hydrophilic site. (Method 3) A method for producing an antifouling member having a film provided on a surface of a substrate, comprising the steps of: a bonding step of bonding a hydrolysate of a silane coupling agent or a condensate of a phosphonic acid derivative to a surface of the substrate; a charge adjustment portion forming step of polymerizing the betaine monomer in the presence of a polymerization initiator after the bonding step; A method for producing an antifouling member, comprising: a hydrophilic portion forming step of forming a hydrophilic portion by adding a hydrophilic monomer and polymerizing the monomer after the charge adjustment portion forming step, (Method 4) The method for producing an antifouling member according to any one of methods 1 to 3, wherein the polymerization initiator is 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] n-hydrate. [Explanation of symbols]
[0093] 11...mouth, 12...bottom surface, 21...first optical path surface, 22...second optical path surface, 23, 24...non-optical path surfaces, 25, 26...analysis light
Claims
1. An antifouling member having a film provided on a substrate, the film has a condensate of a hydrolyzate of a silane coupling agent or a condensate of a phosphonic acid derivative, The film does not contain halogen atoms, The zeta potential of the membrane is −10.0 mV or more and 10.0 mV or less in water at pH=7; An antifouling member, in which, in an X-ray photoelectron spectroscopy analysis (ESCA measurement) of the substrate, the amount of C atoms (atomic %) / the amount of atoms of the element X that is most abundant on the surface of the substrate (atomic %) is defined as A, and in an X-ray photoelectron spectroscopy analysis (ESCA measurement) of the film on the substrate, the amount of C atoms (atomic %) / the amount of atoms of the element X (atomic %) is defined as B, the value of B / A is 2.0 or more and 5.0 or less.
2. 2. The stain-resistant member according to claim 1, wherein the film comprises a copolymer of a monomer having a polarity opposite to that of the substrate, a hydrophilic monomer, and a crosslinking agent.
3. 2. The stain-resistant member according to claim 1, wherein the film comprises a polymer of a betaine monomer.
4. 2. The stain-resistant member according to claim 1, wherein the film comprises a polymer of a betaine monomer and a polymer of a hydrophilic monomer.
5. 5. The stain-resistant member according to claim 2, wherein the hydrophilic monomer is electrically neutral.
6. 5. The stain-resistant member according to claim 2, wherein the hydrophilic monomer is at least one selected from the group consisting of 2-hydroxyethyl methacrylate, N-vinyl-2-pyrrolidone, and polyethylene glycol monomethyl ether methacrylate.
7. The betaine monomer may be 2-(methacryloyloxy)ethyl 2-(trimethylammonio)ethyl phosphate, 2-[[2-(methacryloyloxy)ethyl]dimethylammonio]acetate, 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propionate, 3-[[(3-acrylamidopropyl)dimethylammonio]propanoate, 3-[[2-(methacryloyloxy)ethyl]dimethylammonio]propane-1-sulfonic acid, 4- The antifouling member according to claim 3 or 4, which is at least one selected from the group consisting of [[2-(methacryloyloxy)ethyl]dimethylammonio]butane-1-sulfonic acid, 3-[[2-(acryloyloxy)ethyl]dimethylammonio]propane-1-sulfonic acid, 3-[(3-methacrylamidopropyl)dimethylammonio]propane-1-sulfonic acid, and 3-[(3-acrylamidopropyl)dimethylammonio]propane-1-sulfonic acid.
8. the silane coupling agent is at least one selected from the group consisting of 3-(methacryloyloxy)propyltrimethoxysilane, 3-(acryloyloxy)propyltrimethoxysilane, 3-(methacryloyloxy)propyltriethoxysilane, 3-(methacryloyloxy)propyltriethoxysilane, vinyltrimethoxysilane, triethoxyvinylsilane, allyltrimethoxysilane, allyltriethoxysilane, and (triethoxysilyl)methyl methacrylate; The stain-resistant member according to any one of claims 1 to 4, wherein the phosphonic acid derivative is at least one selected from the group consisting of 2-methacryloyloxyethyl acid phosphate, 2-acryloyloxyethyl acid phosphate, 2-(methacryloyloxy)ethyl phosphate, and acid phosphoxy polyethylene glycol monomethacrylate.
9. 3. The stain-resistant member according to claim 2, wherein the monomer having a polarity opposite to that of the substrate is an amine monomer.
10. The stain-resistant member according to claim 9, wherein the amine monomer is at least one selected from the group consisting of 2-(dimethylamino)ethyl methacrylate, 2-(dimethylamino)ethyl acrylate, 2-(diethylamino)ethyl methacrylate, 2-(diisopropylamino)ethyl methacrylate, and 2-(tert-butylamino)ethyl methacrylate.
11. 3. The stain-resistant member according to claim 2, wherein the crosslinking agent is at least one selected from the group consisting of ethylene glycol diacrylate, ethylene glycol dimethacrylate, polyethylene glycol diacrylate, polyethylene glycol dimethacrylate, and 1,6-hexanediol diacrylate.
12. The stain-resistant member according to any one of claims 1 to 4, wherein the material of the substrate is stainless steel or glass.
13. 5. The stain-resistant member according to claim 1, wherein the film has a charge adjusting portion having a polarity opposite to that of the substrate and a hydrophilic portion.
14. The binding site that binds to the substrate is represented by the following formula (1-1) or the following formula (1-2), The charge adjustment portion is a copolymer of monomers represented by the following formula (2-1), (2-2) and (2-3), or is represented by the following formula (2-4): The stain-resistant member according to claim 13, wherein the hydrophilic site is represented by the following formula (3-1) or the following formula (3-2): 【Chemistry 1】 【Chemistry 2】 【Chemistry 3】 【Chemistry 4】 【Chemistry 5】 【Chemistry 6】 【Chemistry 7】 【Chemistry 8】 (however, In formula (1-1) and formula (1-2), * represents a bonding position with the substrate, ** represents a bonding position with the charge adjustment portion, R1 represents an alkylene group or an oxyalkylene group, R2 represents CH═CH (vinylene group), CH═C (CH 3 ) (isopropenylene group), HC=CH=C(=O)-O (acryloyloxy group), HC=C(CH 3 )-C(=O)-O (methacryloyloxy group), HC=C(CH 3 )-C(=O)-NH (methacryloylamino group), where l is 1≦l≦6; In formulas (2-1), (2-2), and (2-3), R3 represents hydrogen or a methyl group, R4, R5, and R8 each independently represent an alkylene group having 1 to 6 carbon atoms, R6 represents hydrogen or an alkyl group having 1 to 3 carbon atoms, R7 represents an oxyalkylene group having 1 to 3 carbon atoms, and in formula (2-4), ** represents a bonding position with the bonding site, R9 and R10 each independently represent an alkylene group or an oxyalkylene group, R11 represents -COO-, and m is 4≦m≦1000. In formula (3-1) and formula (3-2), *** represents a bonding position with the charge adjustment portion, R8 represents an alkylene group having 1 to 6 carbon atoms, n is 4≦n≦1000, R9 and R10 each independently represent an alkylene group or an oxyalkylene group, and R11 represents —COO - and m is 4≦m≦1000.
15. A member for in-vitro diagnostic devices, comprising the antifouling member according to any one of claims 1 to 4 and 9 to 14.
16. A method for producing an antifouling member having a film provided on a surface of a substrate, comprising the steps of: a bonding step of bonding a hydrolysate of a silane coupling agent or a condensate of a phosphonic acid derivative to a surface of the substrate; a charge adjustment portion forming step of copolymerizing a monomer having a polarity opposite to that of the substrate, a hydrophilic monomer, and a crosslinking agent in the presence of a polymerization initiator after the bonding step; A method for producing an antifouling member, comprising: a hydrophilic portion forming step of forming a hydrophilic portion by adding a hydrophilic monomer and polymerizing the monomer after the charge adjustment portion forming step,
17. A method for producing an antifouling member having a film provided on a surface of a substrate, comprising the steps of: a bonding step of bonding a hydrolysate of a silane coupling agent or a condensate of a phosphonic acid derivative to a surface of the substrate; A method for producing an antifouling member, comprising: after the bonding step, a two-site formation step of polymerizing a betaine monomer at 2.0 mg / ml or more and 12.0 mg / ml or less in the presence of a polymerization initiator to form a charge adjustment site and a hydrophilic site.
18. A method for producing an antifouling member having a film provided on a surface of a substrate, comprising the steps of: a bonding step of bonding a hydrolysate of a silane coupling agent or a condensate of a phosphonic acid derivative to a surface of the substrate; a charge adjustment portion forming step of polymerizing the betaine monomer in the presence of a polymerization initiator after the bonding step; A method for producing an antifouling member, comprising: a hydrophilic portion forming step of forming a hydrophilic portion by adding a hydrophilic monomer and polymerizing the monomer after the charge adjustment portion forming step,
19. The method for producing an antifouling member according to any one of claims 16 to 18, wherein the polymerization initiator is 2,2'-azobis[N-(2-carboxyethyl)-2-methylpropionamidine] n-hydrate.
Citation Information
Patent Citations
Medical capsule
JP1978049873A
Trunk lid of car
JP1986054370A
Cited By
Standard solution, standard sample, method for inhibiting adsorption of standard substance, and kit for immunological measurements
WO2026182143A1